Total phenol content of different varieties of brinjal (Solanum melongena L.) and potato (Solanum tuberosum L.) growing in Bangladesh - Shaheen, Nazma; Kurshed, Ali Abbas Mohammad; Karim, Kazi Muhammad Rezaul; Mohiduzzaman, Md; Banu, Cadi Parvin; Begum, Momtaz; Ishikawa, Yuko Takano (Bangladesh Journal of Botany, 2013)
The total phenol content (TPC) of different varieties of Solanum melongena L. varied from 3.16 ± 0.04 - 7.86 ± 0.33 mg GAE/g of fresh weight (FW). It also revealed that all varieties of Solanum tuberosum L. with peel contained higher TPC than without peel. Comparison between mean TPC of different varieties Solanum tuberosum L. with and without peel on FW basis by independent sample the t-test showed a significant difference (p = 0.003) in TPC. Findings of present study indicate that BARI Begun-8, high yielding varieties of Solanum melongena and Solanum tuberosum with peel are good sources of polyphenols and therefore may contribute as a source of dietary antioxidant. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15909 Bangladesh J. Bot. 42(1): 175-177, 2013 (June)